Performance measurement in the Government of Alberta - Speers, Kimberley (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2005)
Despite the proposed positive aspects of performance measurement, there have been numerous concerns raised about the limitations of being able to measure in a public sector environment. While some people tend to raise more technical concerns, others raised more philosophical concerns about the legitimacy and authenticity of the performance measurement process, given the measures are publicly reported in the government’s business plans and annual reports. In this sense, the legitimacy of performance measurement is threatened because the measures, targets, and results are perceived to be “massaged and manipulated” by management, a central agency, or a communications department. In other words, high-risk measures, such as those that fluctuate, are difficult to attribute, never meet their target, and have a low citizen satisfaction rating, are unlikely to get or remain in a business plan. The third challenge to measuring performance in a government setting is that the external performance measures and targets are linked to department, deputy minister and individual performance plans. This final challenge threatens the validity of the performance measurement framework in the sense that civil servants are likely to choose performance measures and targets that are easy to measure, are stable, and the targets are met or surpassed each fiscal year. It is this subjectivity and the technical challenges of performance measurement that lead to the questioning of the legitimacy and authenticity of reporting on performance in a public sector setting. This subjectivity of both performance and results contributes to the paradox of public reporting. On the one hand, a government can be praised for being transparent in its plans; on the other hand, it can be criticized for publishing politically safe and strategic information for fear of retaliation from the media, opposition parties, and disgruntled citizens. It is this paradox that will be explored in the article under the realm of bureaucratic propaganda.